1965
DOI: 10.1524/ract.1965.4.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Product of Tetravalent Plutonium Hydroxide and Study of the Amphoteric Character of Hexavalent Plutonium Hydroxide

Abstract: The solubility dependence of Pu(0H) 4 as a function of the pn of diluted equilibrating perchloric acid solutions has been studied by covering a wide interval of ps-From the experimental solubility data obtained and some theoretical implications, an attempt has been made to conciliate the extrapolated, experimentally found thermodynamic solubility product with DEBYE-HUCKELS theory on ionic effects to account for the variations observed of the apparent solubility product throughout the different experiments carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

1970
1970
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 1 publication
(6 reference statements)
2
28
2
Order By: Relevance
“…Figures 4 and 5 present similar comparisons of the predicted solubility curves with the experimental results of Np(IV) [29][30][31][32] and Pu(IV), 15,[33][34][35][36] Rai et al 27) As shown in Figs. 4 and 5, the predicted solubility curves are again consistent with the experimental data in acidic region.…”
Section: Speciessupporting
confidence: 61%
See 1 more Smart Citation
“…Figures 4 and 5 present similar comparisons of the predicted solubility curves with the experimental results of Np(IV) [29][30][31][32] and Pu(IV), 15,[33][34][35][36] Rai et al 27) As shown in Figs. 4 and 5, the predicted solubility curves are again consistent with the experimental data in acidic region.…”
Section: Speciessupporting
confidence: 61%
“…4 and 5, the predicted solubility curves are again consistent with the experimental data in acidic region. Although the data of Perez-Bustamente 35) are much higher than the predited solubility, possible disproportionation of Pu(IV) has been pointed out by Rai. 33) Similarly to the above, it is also noticed that there are some contributions of colloid formation to the observed solubility data in near neutral and higher pH region.…”
Section: Speciesmentioning
confidence: 97%
“…At each concentration of Pu VI , the titration curves at different temperatures start to differ from each other at pC H % 3.5, indicating that the hydrolysis of Pu VI becomes observable by potentiometry when pC H is above 3.5. After testing various combinations of the hydrolysis species suggested in the previous literature, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]37] the best fit of the titration data was obtained by including three hydrolysis reactions [Eq. (3)- (5)] in the calculation.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, such data are scarce, highly scattered for 298.15 K, and unknown for elevated temperatures. [1][2][3] A literature survey shows that a total of seventeen studies on the hydrolysis of Pu VI have previously been conducted at or near 298.15 K. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] A number of hydrolyzed species, (PuO 2 ) m (OH) n (2mÀn) + , have been postulated, including monomeric (m = 1 and n = 1, 2, 3), dimeric (m = 2 and n = 2, 3, 4, 5), trimeric (m = 3 and n = 5), and tetrameric species (m = 4 and n = 7). [2,18,19] Hydrolysis constants (*b n,m for the reaction mPuO 2 2 + +nH 2 O = (PuO 2 ) m (OH) n (2mÀn) + +nH + ) at or near 298.15 K have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…From this equation it can be seen that a very high potential would prevail for the system PuO=;^ "/PuOj, (OH)., at pH 0. Line 4 represents Equation 4. If the solubilized species of hexavalent plutonium PuOg(OH),-is nonexistent, and if hexavalent plutonium is not amphoteric at all, then lines 2 and 4 should be removed from Figure 1, and the potential-pH diagram should contain only line 1 and line 3 and its dotted extension.…”
Section: Instability Of Heptavaient Plutonium In Water Solutionsmentioning
confidence: 99%